Here is the answer for the question – **Which quadratic equation is equivalent to (x – 4)2 – (x – 4) – 6 = 0?**. You’ll find the correct answer below

### Which quadratic equation is equivalent to (x – 4)2 – (x – 4) – 6 = 0?

**The Correct Answer is**

**u2 – u – 6 = 0 where u = (x – 4)**

### Reason Explained

u2 – u – 6 = 0 where u = (x – 4) is correct for Which quadratic equation is equivalent to (x – 4)2 – (x – 4) – 6 = 0?

Thankyou for using answerout. We hope you get all your answers here. If you have any special questions, you can comment to ask us.

Latest posts by Alex Timmons (see all)

- Christina is wanting to utilize quantitative-based research to answer her marketing research problem. As such, you recommend that she consider using __________ as a primary research method. - February 6, 2023
- If the column of mercury in a barometer stands at 72.6 cm, what is the atmospheric pressure? (The density of mercury is 13.6 103 kg/m3 and g = 9.80 m/s2) - February 6, 2023
- Polarity - February 6, 2023